Validation of the Turkish version of medication regimen complexity index among elderly patients - OKUYAN, BETÜL; SANCAR, MESUT; AY, NADİYE PINAR (WILEY, 2016)
ObjectiveThe aim of this study was to validate the Turkish version of the Medication Regimen Complexity Index' (MRCI). MethodsThis validation study has been conducted in prescriptions of the first 100 elderly patients who had visited the pharmacy for their prescription refill to evaluate convergent and divergent validity of the Turkish version. The reliability of the Turkish version was assessed with inter-rater and test-retest analysis after its translation and cultural adaptation. ResultsThe mean age of the 100 patients (53 women) was 74.9years (SD=7.58, 65-95). The scale showed high inter-rater reliability and test-retest reliability for the total and subscale scores (p<0.05). A strong and positive correlation between the number of medications in a prescription and the total Medication Regimen Complexity Index scores (r=0.930, p<0.001) was determined. There were no statistically significant differences between age, gender and MRCI scores (p>0.05). ConclusionThese results show that the Turkish version of MRCI is a reliable and valid tool in elderly patients.
Keywords: clinical pharmacy; medication complexity; elderly; polypharmacy; ADVERSE DRUG EVENTS; UNPLANNED HOSPITAL READMISSIONS; OLDER-PEOPLE; POLYPHARMACY; INTERVENTION; INPATIENTS; ADHERENCE; DISCHARGE; ADULTS